Melt pond depth retrieval applying airborne spectral imaging and the potential of a new RGB band approach - Rosenburg, S.; Jäkel, E.; Wendisch, M. (Universität Leipzig, 2023)
Melt ponds are important features on summer Arctic sea ice leading to a surface albedo reduction and thereby altering the energy budget. Besides the spatial pond coverage, the melt pond depth is of importance in context of meltwater volume distribution across the sea ice surface. In this study, the melt pond depth is retrieved based on airborne reflectance measurements performed in the framework of an Arctic field campaign. An already existing approach uses the spectral reflectance slope and is widely independent of the pond ice bottom reflectance contribution. However, the surface coverage of the imaging spectrometer, providing the required spectrally resolved information, is limited due to the narrow field of view. To capture a larger number of melt ponds, a commercial digital camera with fisheye-lens provides reflectances in the red, green, and blue (RGB) spectral ranges. To retrieve the melt pond depth a new RGB band approach was developed and validated by the established spectral retrieval approach. The depth deviation of the approaches ranged between 0.1 cm and 27.6 cm depending on prior information on the pond ice bottom reflectance. Schmelztümpel stellen wichtige Oberflächenmerkmale des arktischen Meereises im Sommer dar, da sie die Albedo senken und somit Einfluss auf das Energiebudget haben. Neben der Fläche, die die Tümpel bedecken, ist ebenfalls deren Tiefe im Rahmen der Schmelzwasserverteilung relevant. In dieser Studie wird die Schmelztümpeltiefe von flugzeuggetragenen Reflektanzmessungen abgeleitet, die während einer Messkampagne in der Arktis durchgeführt wurden. Ein bereits bestehender Ansatz verwendet den spektralen Reflektanzanstieg und ist weitgehend unabhängig von der Reflexion am Eisboden des Tümpels. Jedoch ist die räumliche Abdeckung des bildgebenden Spektrometers, das spektral aufgelöste Messungen ermöglicht, durch den schmalen Öffnungswinkel des Instruments limitiert. Um eine größere Anzahl von Tümpeln zu beobachten, kann eine kommerzielle Digitalkamera mit Fischaugenlinse verwendet ...